THE NORDIC RESPONSE TO THE UKRAINE WAR - Jović-Lazić, Ana (The Review of International Affairs, 2026)
This study examines how the Russian invasion of Ukraine affects the security strategies of Nordic countries. In light of this increased threat, Sweden, Finland, and Denmark have reevaluated their defence strategies. Finland and Sweden, long-time adherents of neutrality and nonalignment, joined NATO; Denmark integrated entirely into the European Union’s defence cooperation. A comparative method was used to examine changes in the policies of these countries. Theoretical frameworks, such as neorealism, constructivism, and crisis management theory, are used to examine the reasons behind their choices. Neorealism explains how views on the Russian threat have influenced military integration approaches, while constructivism explores the influence of identity and norms in determining foreign policy. Crisis management theory explains how Nordic nations have adjusted their security policies to respond to international security challenges. Through qualitative analysis of documents and discourse analysis, the motivations influencing these decisions were explored. The findings indicate that the perceived threat from Russia has primarily driven a change in the defence policies of the Nordic countries, which will have long-term implications not only for them but also for the future role of NATO and the EU in Northern Europe. In doing so, this study contributes to understanding how these states have shaped future collective security in Europe.